Strength Prediction of Rectangular FRP-Reinforced Concrete Columns Under Eccentric Loading - Nam Nguyen Van; Hiep Dang Vu; Duy Nguyen Phan (Advances in Technology Innovation, 2026)
This study aims to develop an analytical model for evaluating the load-carrying capacity of rectangular fiber-reinforced polymer (FRP) reinforced concrete columns under eccentric loading. In the proposed model, the contribution of FRP bars in compression is considered, with their compressive strength estimated as a fraction of tensile strength. Meanwhile, the effects of confinement, tension stiffening, and second-order effects are conservatively neglected. Two main failure modes, namely concrete crushing and FRP rupture, are distinguished by the balanced failure condition. This model applies strain compatibility with the plane section and constitutive laws to derive stress-strain distributions across the cross-section. Then, the model is validated against 91 experimental results covering diverse sections, strengths, and eccentricities (e/h = 0.1-1.0), showing high accuracy (mean: 0.932; RMSE: 0.154; COV: 22.9%; SD: 0.145; r: 0.84) and outperforming ACI CODE-440.11. Analysis results also show that compressive FRP reinforcement contributed between 0.94% and 22.3% to the column strength.